(untitled) (The Journal of Nuwakot Adarsha Multiple Campus, 2024)
In her collection of short stories Games at Twilight and Other Stories (1978) popular Indian literary figure Anita Desai (b. 1937-) has included eleven different stories. Among these stories, one story A Devoted Son depicts the societal norms of middle-class Indian family in an Indian village. Happiness of parents in the success of their son and the responsibilities of a son towards his mother and father is presented in the story. Rakesh, as the major character of the story, is a role model for following societal norms and becomes the source of inspiration for the new generation to be the devoted son/daughter to their parents. Our society is our home and the societal norms that exist in our society are our identity. This theme is the major focus of Desai in this story. Care of parents during their old age, economic management to run the family, harmonious relations among the members of society, sharing sorrows and happiness with neighbors etc. are the societal norms found in the story. When the text is observed through the theoretical perspective of cultural materialism, this paper wants to clarify that the writer has used societal norms in her story to inform the new generation that it is a part of our culture.